(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
Concrete sandwich panel [CSP] is an innovative structural construction system. It is two or more layers of concrete separate by lightweight layers. The present work, the one-way sandwich panels are comprised of two lightweight concrete layers, between them a layer of cork, the dimensions of the slabs were (1100mm total length × 400 mm width × 90mm thickness). The outer concrete layers were connected by steel bar in the shape of truss. An experimental program was carried out on four slabs, one of them was solid slab while the three other slabs were sandwich slabs. The main variable of this study was the type of course aggregate which used in the outer concrete layers. The slabs have been tested as a simply support span under two points load. Experimental results proved that the using of sandwich panels will have enhanced many properties such as toughness, ductility and maximum value of deflection, in addition to the main benefit is a total weight reduction. The differ in the type of coarse aggregate considerably influences the structural behavior of the panels.